Analisis code switching di dalam video vlog YouTube Leonardo Edwin - Badriyah, Nur Lailatul (Maliki Interdisciplinary Journal, 2024)
This research aims to analyze the code switching used in Leonardo Edwin’s YouTube vlog video titled “Nyaris Ngomong Selain Inggris Tambah Sambel Pedas!!! Challenge Cuman Boleh Ngomong Inggris Bareng Tomo” along with the types of code switching. In this study, the researchers used theory Poplack (2004) to analyze the types of code switching. There are several methods used by the author to find data, namely by searching for videos, then watching and listening to videos, and analyzing the code switching in the videos. The researcher found four code switching types of Inter-Sentential Switching and five code switching types of Intra-Sentential Switching.